مكافحة الفساد: سعي لوقاية الفساد من خلال التعليم - Ahmad Lathif (AT-TURATS, 2015)
Corruption is not only related to prosecution of the perpetrators, but more importantly also to the prevention, as it is better to prevent than to treat. To prevent it, it is important to integrate anti-corruption education with lessons at schools. Anti-corruption education is an essential effort to combat corruption. Anti-corruption education should be directed at the providing an understanding of the harm of corruption to the State, society and religion so as to prevent it from recurring in the future. The phenomenon of corruption also originates from education that tends to ignore a mainstream or paradigm to behave honestly both in words and actions. Anti-corruption education should put emphasis on moral values. Morality should become the main preventive measure for combating corruption since it will shape one’s behavior. Anticorruption education in school at least is related to three aspects: first, integrating anti-corruption materials into existing subjects, especially the curriculum of 2013 which states that all subjects containing spiritual and social values should be in line with the anti-corruption materials; second, corruption education should be included in extra-curricular activities in schools or other incidental activities which can also be done by collaborating with parties outside the school; third, the anti-corruption education can also be done through habituation in all school activities such as homework, worship and so forth.